ENLIGHTENED PROGRAMME VERSUS REPUBLICAN PROGRAMME IN THE NEOGRANADIAN EDUCATIONAL ISSUE (2011)
The establishment of the Republican State marks a inflection epoch which have in education field connections with the change processes which were developed over the last thirty years of the eighteenth century, as well as in the debates about how to educate people of the nascent Republic, which were kept alive for most of the nineteenth century. The discussion about education was based on three issues: the curriculum, the relationship between higher education and the Church, and the controversy between traditional sciences and practical science. As well as, about what kind of knowledge to promote or if was necessary to keep the Scholastic method and its emphasis on rhetoric, literature and law, or to promote the study of practical sciences related to knowledge based on experience.